2013
DOI: 10.1509/jmr.13.0124
|View full text |Cite
|
Sign up to set email alerts
|

Internet versus Television Advertising: A Brand-Building Comparison

Abstract: Many advertisers are reluctant to shift a large proportion of their advertising budgets to the Internet because they still view television advertising as the main vehicle for building a brand. Using a unique and rich data set comprising 20 campaigns across a variety of industries, this study demonstrates that Internet ads perform on par with television ads on the brand-building metrics that advertisers use and trust. The authors extend traditional brand–message recall measurements to facilitate comparisons bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 11 publications
2
30
0
3
Order By: Relevance
“…In line with previous research (Kim and Ko 2012;Bruhn, Schoenmueller, and Schäfer 2012;Draganska, Hartmann, and Stanglein 2014), our results showed an influence of media channels on brand equity. Similar to Bruhn et al (2012), we found that media channels had significant effects on brand image perceptions.…”
Section: Theoretical Implicationssupporting
confidence: 92%
See 1 more Smart Citation
“…In line with previous research (Kim and Ko 2012;Bruhn, Schoenmueller, and Schäfer 2012;Draganska, Hartmann, and Stanglein 2014), our results showed an influence of media channels on brand equity. Similar to Bruhn et al (2012), we found that media channels had significant effects on brand image perceptions.…”
Section: Theoretical Implicationssupporting
confidence: 92%
“…First, if media type (traditional vs. social media) influences brand personality as hypothesized above, and brand personality has an effect on brand equity dimensions as reported in the literature, then the media type should have an indirect effect on brand equity and brand response through brand personality. Previous studies reported associations between media types (traditional and social media) and brand equity (Kim and Ko 2012;Bruhn, Schoenmueller, and Schäfer 2012;Draganska, Hartmann, and Stanglein 2014), but did not examine the mediating role of brand personality. Similarly, our model also implies an indirect effect of brand personality on brand response through brand equity.…”
Section: H3mentioning
confidence: 97%
“…To minimize such brand-specific effects, we performed additional analysis where we calculated mean attitude across the three target brands (α = 0.97) and used this mean brand attitude as the dependent variable in analysis of variance. Notably, past research has used a similar approach of combining evaluations across brands to assess overall advertising effectiveness (Berger, Wagner, & Schwand, 2012;Draganska et al, 2014). As before, we conducted a one-factor (Web site type: social vs. commercial) ANOVA on mean attitude toward the three brands along with the covariates of product involvement and brand familiarity.…”
Section: Additional Analysismentioning
confidence: 99%
“…Online display advertising (ODA, hereafter) refers to display ads that Web site visitors see alongside other content (Goldstein, Suri, McAfee, Ekstrand-Abueg, & Diaz, 2014). These ads are graphic images that vary in size, shape, animation, and duration, and come in different formats such as banners, skyscrapers, and wallpapers (Draganska, Hartmann, & Stanglein, 2014). ODA is an important form of Internet advertising, with a total ad spend of $27 billion in the United States alone during 2015 that represents 24% growth in spending over 2014 (eMarketer, 2015a).…”
mentioning
confidence: 99%
“…Los anuncios presentan la estructura clásica (trama-nudo-desenlace) con una duración superior a la habitual (medía 2'21", SD = 1'30"). En este sentido encontramos diferencias respecto a la publicidad televisiva tradicional, la cual establece duraciones entre los 10 y los 120 segundos (Escribano, Fuentes & Alcaraz, 2007;Peters & Bijmolt, 1997;Prado et al, 2007), de forma que se nos plantea cierta dificultad a la hora de denominar la publicidad que se usa habitualmente en YouTube, derivando hacia nuevas clasificaciones que abracen e integren conceptos clásicos, como el del spot publicitario y filme publicitario (Gutiérrez, 2005) dentro de las nuevas plataformas (Draganska, Hartmann & Stanglein, 2014).…”
Section: Discusión Y Conclusionesunclassified